PEMANFAATAN FUNGI Aspergillus flavus, A. tereus DAN Trichoderma harzianum UNTUK MENINGKATKAN PERTUMBUHAN BIBIT Rhizophora apiculata DI DESA PULAU SEMBILAN KABUPATEN LANGKAT - Monalia Hutauruk; Yunasfi Yunasfi; Mohammad Basyuni (Program studi Kehutanan USU, 2015)
Mangrove is a forest that it is affected by tides. Indonesia is one of countries that has the largest mangrove forest in the world. Nowdays, the area has been reduced due to the degradation of mangrove forests. This degradation can be addressed with rehabilitation. This study used the fungi of A. flavus, A. tereus and T. harzianum against R. apicuta seedlings which is one of the species used for the rehabilitation of mangrove forests. The research was conducted on August 2014 untill January 2015 using a completely randomized design (CRD) with A. flavus, A. tereus and T. harzianum treatments and with five replications. Results showed that treatment of T. harzianum provided seedlings, the best growth of R. apiculata where the average height of 16.06 cm, diameter of 0.676 cm, a leaf area of 259.68 cm2, and a total of 19 g dry weight compared to the control with average height of 10.06 cm, 0,619 cm of diameter, leaf area of 146.64 cm2, and the total dry weight of 10.92 g.Key word: fungi, mangrove, Rhizophora apiculata, seedling